A practical guide to adult vaccination for patients with autoimmune inflammatory rheumatic diseases in India - Sharath Kumar; Prasandeep Rath; Anand Narayan Malaviya (Indian Journal of Rheumatology)
Autoimmune inflammatory rheumatic diseases have intrinsic increased risk of infection. The medications used in these diseases may further increase the infection risk. Therefore, vaccinations have gained increasing importance in preventing them in a most cost-effective manner. In this “practical guide,” the vaccines, their schedules, pricing, and the lifetime cost analysis, specifically for the Indian patients, are described in clear, concise language. Case scenarios have been used to further simplify the understanding of the vaccination schedules. This document can be kept in the clinic for day-to-day help in ensuring that the patients are properly covered against these preventable infections.